2021
DOI: 10.1088/1361-665x/abd42b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of installation position of fin-shaped rods on wind-induced vibration and energy harvesting of aeroelastic energy converter

Abstract: The influence of fin-shaped rod (FSR) with different installation positions on wind-induced vibration and energy harvesting of a cylinder-based aeroelastic energy harvester are studied by experiments and simulations. Two FSRs are installed symmetrically on the surface of a circular cylinder, and the coverage angle of each FSR is 20°. The installation position of FSRs on the cylinder is represented by the placement angle, θ, which varies in the range of ±160°. And the tested wind speed range is 0–6.8 m s−1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The flow-induced vibration constitutes the first step toward converting the hydrokinetic energy into mechanical energy. According to the underlying mechanisms, common FIV phenomena can be classified into galloping, 11,12 vortex-induced vibration (VIV), 13,14 flutter, 15,16 and buffeting. 17 I summarizes and compares the aerodynamic response characteristics of VIV, galloping, and flutter in detail.…”
Section: A Fluid-structure Interactionmentioning
confidence: 99%
“…The flow-induced vibration constitutes the first step toward converting the hydrokinetic energy into mechanical energy. According to the underlying mechanisms, common FIV phenomena can be classified into galloping, 11,12 vortex-induced vibration (VIV), 13,14 flutter, 15,16 and buffeting. 17 I summarizes and compares the aerodynamic response characteristics of VIV, galloping, and flutter in detail.…”
Section: A Fluid-structure Interactionmentioning
confidence: 99%
“…The partition or splitter plate is a fine rigid plate arranged parallelly to the flow. Numerous experimental and numerical studies can be found where the detached flat plate is applied as a control instrument by varying its position or length (Aabid et al, 2019;Ali et al, 2012;Anderson et al, 1997;Apelt et al, 1973Apelt et al, , 1975Bruneau et al, 2014;Dehkordi et al, 2011;Ding et al, 2021;Doolan, 2009;Hassanzadeh Saraei et al, 2021;S. Ul Islam et al, 2015;Shams Ul Islam et al, 2014;Liu et al, 2016;Maruai et al, 2018;Mat Ali et al, 2011;Nidhul et al, 2015;Ozono, 1999;Park et al, 2013;Rashidi et al, 2016;Roshko, 1954;Sakamoto et al, 1997;Turki, 2008;Zhou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For the ambient environment, there are various renewable energy technologies [5], such as solar energy [6][7][8], wind energy [9][10][11], and vibration energy [12][13][14][15][16]. Ocean wave energy exists at the surface of the ocean in the form of kinetic and potential energy.…”
Section: Introductionmentioning
confidence: 99%